A new standardisation and selection framework for real-time image dehazing algorithms from multi-foggy scenes based on fuzzy Delphi and hybrid multi-criteria decision analysis methods - Al-Juboori, Aos A. Z.,Ansaef (Tanjung Malim, 2021)
A new standardisation and selection framework for real-time image dehazing algorithms from multi-foggy scenes based on fuzzy Delphi and hybrid multi-criteria decision analysis methods by Al-Juboori, Aos A. Z.,Ansaef